Kaidah Keyakinan atas Keraguan dan Implementasinya dalam Urusan Pemerintahan - Aulia Nurrosidha; Jihan Fahriyyah; Rafli Fadhil Fazran; Annas Alpiqri (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This paper produces an analysis of fiqh rules “al-yaqin la yuzal bi al-syak” and its implementation in government affairs. This study uses content analyst technique, on existing written data. This research finds that the description of the “al-yaqin la yuzal bi al-syak” fiqh method is that if someone has believed in a case, then what has been believed cannot be removed with doubt (things that are still in doubt). This rule emphasizes that a law that is based on belief cannot be influenced by doubts that arise later. Because before the doubt arose, he had believed in the validity of the taharah that had been done. Thus, this rule shows us the perfection of the Islamic religion that we love. If we apply this rule, then we will be more convinced that Islam is a religion that brings mercy to the universe.